(untitled) (Medical Forum Monthly, 2023)
Objective: To evaluate the association between severity of squamous cell carcinoma and quality of life in patients Study Design: Descriptive cross sectional study Place and Duration of Study: This study was conducted at the Department of Oral & Maxillofacial Surgery, Jinnah Postgraduate Medical Centre, Karachi from July 2021 to January 2022. Materials and Methods: Total of 161 Patients of squamous cell carcinoma diagnosed on biopsy samples were enrolled in study. Main variables of study were severity of disease (stage I, II, III, IV) and quality of life score (FACT H & N). SPSS Version 23 was used for data analysis. Variables were presented in form of mean SD and frequency percentages. Results: One hundred sixty one patients were enrolled, in our study. The average age of the patients was 32.05±4.71 years. The average score for physical, social, emotional and functional well-being were shown in table. II. Further, the mean score for additional concerns, trail outcome index, FACT-G and FACT H&N was 25.02±4.76, 64.96±7.21, 86.81±13.01 and 112.92±23.84, respectively. Conclusion: There is a strong association between quality of life (FACT H & N) score and severity of squamous cell carcinoma. Patients in advance stage of cancer (stage III and IV) were observed with more decrement in quality of life than early stages (I and II).